2023
DOI: 10.1039/d2nj04856f
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the unrecognized flammability of deep eutectic solvents for green rocket fuels

Abstract: A new strategy for hybrid deep eutectic solvent (DESs) that are hypergolic with hydrogen peroxide was developed, in which the intruduction of transition metal components can effectively release the latent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…In the 1 H NMR spectrum, two peaks around  = 9.10-9.30 and 8.20-8.5 ppm can be assigned to the two hydrogens in triazole ring. In the 13 C NMR spectra, two peaks around  = 149 ppm and 144 ppm can be assigned to the two carbons in 1,2,4-triazole ring. In the 11 B NMR spectrum, a singlet peak at  = ca.…”
Section: Figure 1 Selected Structures and Properties Of Previously Re...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1 H NMR spectrum, two peaks around  = 9.10-9.30 and 8.20-8.5 ppm can be assigned to the two hydrogens in triazole ring. In the 13 C NMR spectra, two peaks around  = 149 ppm and 144 ppm can be assigned to the two carbons in 1,2,4-triazole ring. In the 11 B NMR spectrum, a singlet peak at  = ca.…”
Section: Figure 1 Selected Structures and Properties Of Previously Re...mentioning
confidence: 99%
“…There is little doubt that this step significantly increases reaction time and costs, 12 hence it is particularly crucial to incorporate hypergolic reaction groups into propellant fuels using a straightforward technique. 13…”
Section: Table 1 Physical Properties and Specific Impul...mentioning
confidence: 99%
See 1 more Smart Citation
“…DESs, after all, belong to a huge class of compounds, and are composed of at least two components, and the physicochemical properties of the systems would depend on the types of intermolecular interactions arising between constituent molecules. DES (or ILs) are not necessarily nonflammable, for example, it has recently been shown that DESs can be hypergolic . In addition, their toxicity is not automatically determined by the overall toxicity and cytotoxicity of the starting materials, many DESs exhibit higher toxicity than the individual components …”
Section: When the Chemistry Is Not So Simple: Species Of Intermediate...mentioning
confidence: 99%
“…DES (or ILs) are not necessarily nonflammable, for example, it has recently been shown that DESs can be hypergolic. 263 In addition, their toxicity is not automatically determined by the overall toxicity and cytotoxicity of the starting materials, many DESs exhibit higher toxicity than the individual components. 264 A potential reason that the DES field currently is publishing misconceptions (as the IL field did), as elegantly stated in one paper, 265 is that a fundamental understanding of the IL field proceeded simultaneously with their application development, whereas the progress in DES applications happened too fast, and their fundamental understanding did not keep up with it.…”
Section: Difficulties With Classificationmentioning
confidence: 99%